Pengaruh Model Pembelajaran RADEC (Read-Answer-Discuss-Explain-Create) dengan Pendekatan STEM Berbantuan Media Google Sites terhadap Kemampuan Literasi Sains dan Hasil Belajar IPAS di SD - Diana Cantika Aprillia (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research is motivated by the low scientific literacy skills that have an impact on students' science learning outcomes. This study aims to determine the effect of the RADEC learning model with the STEM approach assisted by Google Sites media on scientific literacy skills and science learning outcomes in elementary schools. This study uses a quasi-experimental design with a pretest-posttest control group design. The sampling technique used is purposive sampling by selecting class VA as the experimental class with 28 students and class VB as the control class with 29 students. The instrument in the form of essay questions as many as 6 questions is used to measure literacy skills, the instrument in the form of multiple-choice questions as many as 20 questions is used to measure cognitive learning outcomes, and observation sheets with a rating scale of 1 to 4 to measure psychomotor learning outcomes. The results of the test data collection were then analyzed using the ANACOVA test assisted by SPSS version 26. The results of the hypothesis test for scientific literacy skills obtained a significance value of 0.006
Reaploud Repisitory February 2026_Hasyim
Keywords: Google Sites; learning outcomes; RADEC; scientific literacy; STEM